QTL Analysis of Type I and Type IIA Fibers in Soleus Muscle in a Cross between LG/J and SM/J Mouse Strains - Carroll, Andrew M.; Palmer, Abraham A.; Lionikas, Arimantas (Frontiers in Genetics, 2012)
Properties of muscle fibers, i.e. their type, number and size, are important determinants of functional characteristics of skeletal muscle, and of the quality of meat in livestock. Genetic factors play an important role in determining variation in fiber properties, however, specific genes remain largely elusive. We examined histological properties of soleus muscle fibers in two strains of mice exhibiting a 2-fold difference in muscle mass, LG/J and SM/J, and their F2 intercross. The total number of muscle fibers (555 ± 106) did not differ between the strains or between males and females. A higher percentage of type I fibers was observed in LG/J than SM/J strain (P<0.001) in both males (45±3% vs 37±4%) and females (58±4% vs 41±3%). Across strains, females had a higher percentage of type I fibers than males (P<0.001), and the sex effect was greater in LG/J strain (strain-by-sex interaction, P<0.001). The cross-sectional area (CSA) did not differ between type I and type IIA fibers, it was greater in LG/J than SM/J strain (1365±268 μm2 vs 825±229 μm2, P<0.001). Three significant QTL affecting CSA for type I and type IIA fibers mapped to chromosomes 1, 6 and 11 and three suggestive QTL for percentage of type I fibers to chromosomes 2, 3, and 4. Within each significant QTL, regions of conserved synteny were also implicated in variation of similar traits in pig. Our results provide the evidence that the intercross between the SM/J and LG/J strains is a promising model to search for genes affecting muscle fiber properties.